2020
DOI: 10.17509/ijal.v9i3.23207
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia Islamic senior high school students’ English learning conceptions and strategies

Abstract: This study was inspired by previous studies of how students’ learning influences their learning belief and in turn, their strategies. Unfortunately, few studies concern learners’ conceptions of learning, in particular in learning English; and paid less attention to senior high school students level. With the intention to identify Islamic senior high school. Interview and both close and open questionnaires were used to collect relevant data. To identify students’ conception, Purdie and Hattie’s COLI items were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…Similarly, findings with Islamic high school students in Indonesia were discovered. According to the findings of this study, students tend to employ the surface level in their learning approach (Mulyani et al 2020). According to Mulyani et al (2020) research's the majority of high school students regard studying as an obligation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Similarly, findings with Islamic high school students in Indonesia were discovered. According to the findings of this study, students tend to employ the surface level in their learning approach (Mulyani et al 2020). According to Mulyani et al (2020) research's the majority of high school students regard studying as an obligation.…”
Section: Discussionmentioning
confidence: 72%
“…According to the findings of this study, students tend to employ the surface level in their learning approach (Mulyani et al 2020). According to Mulyani et al (2020) research's the majority of high school students regard studying as an obligation. It concludes that according to research conducted in the Indonesian context, the student learning approach is linked to the student's learning objectives (Hulreski et al, 2020;Meeks et al, 2013;Mulyani et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Learning strategies were also noteworthy for each learner. A language learner needed the language learner to make learning easier, faster, more enjoyable, and more effective to achieve specified results (Mulyani et al, 2020).…”
Section: Graphic 3 Students' Knowledge On the Difference Between Madrasah Basra And Kufamentioning
confidence: 99%
“…In addition, the researchers reported that across groups internal consistency reliability indexes ranged from .45 to .92, with a mean of .74 and a median of .76 (Purdie & Hattie, 2002). Ever since, a great number studies that used COLI across different contexts and students" cultural backgrounds (e.g., Mulyani, Suherdi, & Sundayana, 2020;Pinto, Bigozzi, Vettori, & Vezzani, 2018;Chaleta, 2018;Chan, 2011;Peterson, Brown, & Irving; reported satisfactory psychometric properties of the inventory. The present used the Conceptions of Learning Inventory (COLI).…”
Section: Conceptions Of Learningmentioning
confidence: 99%